التنظيم القانوني للمقاصة الإلكترونية للشيكات بين المصارف الفلسطينية - عُلا سمرين صالح محامده (My University, 2024)
Abstract The study examines electronic clearing as a banking process that converts data from paper checks into a specialized information program through a specific mechanism, enabling electronic settlement of checks. The researcher also explores the fundamentals of electronic clearing, starting with a preliminary study of its basics and its role within commitment provisions. Furthermore, the study delves into the legal organization of clearing in Palestine, discussing the nature and characteristics of electronic clearing, along with its operational procedures. It also involves discussing the legal organizationof electronic transactions, the essential legal requirements for conducting these transactions, examining the electronic clearing record as a form of evidence, understanding the legal implications of electronic transactions, and the importance of outlining the responsibilities of banks within the clearing system towards their customers. The researcher employs a descriptive and comparative analytical approach to thoroughly understand electronic transactions in all their facets, including an examination of the regulations governing electronic transactions in Palestine and their effectiveness. Keywords: Legal Organization; Electronic Transactions; Palestinian Financial Institutions.